Broadcasting Birth Control : Mass Media and Family Planning - Parry, Manon (Book collections on Project MUSE., 2013)
Traditionally, the history of the birth control movement has been told through the accounts of the leaders, organizations, and legislation that shaped the campaign. Historians have recently begun examining the cultural work of printed media, including newspapers, magazines, and novels in fostering support for the cause. This book builds upon this new scholarship on the women's reproductive health movement to explore the films and radio and television broadcasts developed by twentieth-century birth control advocates to promote family planning in the United States, and in the expanding international arena of population control.